Recipes Between Cultures: Muslim Women’s Food, Memory, and Identity in Diana Abu-Jaber’s The Language of Baklava and Life Without a Recipe - Tamaliya Mu'tirrahmah (Jurnal Bahasa, Sastra, dan Studi Amerika, 2026)
This study explored how Diana Abu-Jaber's memoirs, The Language of Baklava: A Memoir and Life Without a Recipe, portrayed the journey of Muslim women through food. The research used the lenses of Muslimah narratives, literary devices, and intertextuality to analyze the profound connection between culinary experience and identity in a diasporic context. The paper argued that food is key to this journey in three main ways: (1) it acts as a medium for cultural preservation and identity affirmation; (2) it expresses personal agency, emotional healing, identity negotiation; and (3) it serves as a site for intergenerational storytelling and cultural continuity. The analysis found that food, particularly traditional dishes like baklava, served as a source of emotional comfort for the women, helping them maintain their heritage and define a new, hybrid Arab-American self. Furthermore, the kitchen provided an important space where women gained social authority and practiced self-determination to cope with cultural displacement. The study concluded that food in these memoirs is a dynamic tool actively used by Muslim women to assert their self-worth and ensure their cultural identity remains vibrant across geographical boundaries.